A Human/Mouse Chimeric Monoclonal Antibody against Intercellular Adhesion Molecule‐1 for Tumor Radioimmunoimaging - Yamamura, Miyuki (Jpn J Cancer Res, 1996)
A mouse‐human chimeric antibody for intercellular adhesion molecule‐1 (ICAM‐1) was established by using heavy chain loss mouse mutant hybridoma and human immunoglobulin expression vector. The HA58 hybridoma secreted anti‐ICAM‐1 monoclonal antibody (MoAb) (IgG1, k). The gene of the mouse variable region of heavy chain was amplified and cloned by the polymerase chain reaction technique directly from the HA58 hybridoma RNA. The variable region of heavy chain was joined with an expression vector which contains human γ1 constant gene. The expression vector was transfected into heavy chain loss mutant cells HA58‐7, which produced only murine immunoglobulin light chains. The resultant chimeric MoAb HA58, chHA58, retained full‐binding reactivity to ICAM‐1 compared with murine HA58 parental antibody. The chimeric MoAb chHA58 showed little antibody dependent cell‐mediated cytotoxic activity against cultured tumor cells. Biodistribution studies with (99m)Tc‐labeled chHA58 in nude mice bearing human gastric carcinoma JRST cells demonstrated that the tumor‐blood ratio was 1.55 at 18 h after injection, when the tumors were clearly visible in gamma scintigraphy. These data suggest that chHA58 may be of practical use for radioimmunoimaging of a wide variety of tumors.